Strategi Penguatan Literasi di Sekolah - Joko Purwanto; Yuli Widiyono; Nurhidayati Nurhidayati; Ica Melvira Pratiwi; Lia Safira; Nurul Fitriani (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of technology and information is increasingly rapid. This of course requires the ability of students to face and anticipate it. One of the abilities that students must have is literacy. However, in fact, students in Indonesia still really need strengthening in the field of literacy. Various existing surveys show that these two capabilities have not experienced significant improvement. The same thing was also experienced by students at SMA Negeri 6 Purworejo. For this reason, a comprehensive and continuous effort is needed to improve this capability. Based on these situations and conditions, the Muhammadiyah University Purworejo Service Team built a collaboration with SMA Negeri 6 Purworejo to improve literacy skills for the school's residents. The theme raised was